Thermodynamics. - Gupta, S. C. (2007)
Thermodynamics is designed for the first course on thermodynamics offered to undergraduate students of mechanical engineering. The book presents the Macroscopic (classical) and Microscopic (statistical) thermodynamics including applications to power cycles, and aims to create an analytical mind in the reader to solve problems.
9.2.1 Pressure Calculation -- 9.2.2 Velocity Distribution -- 9.2.3 Average Root Mean Square Velocity and Most Probable Speed -- 9.2.4 Energy Distribution Function -- 9.3 Results from the Macroscopic Approach -- 9.3.1 Collision with a Moving Wall -- 9.3.2 Specific Heats of a Gas -- 9.3.3 Transport Processes in Gases -- 9.4 Statistical Thermodynamics -- 9.4.1 Distribution of Molecules in Energy Levels -- 9.4.1.1 Maxwell-Boltzman (MB) Statistics -- 9.4.1.2 Bose-Einstein (BE) Statistics -- 9.4.1.3 Fermi-Dirac (FD) Statistics -- 9.4.2 Thermodynamic Probability of the Most Probable State -- 9.4.3 Entropy -- 9.4.4 Distribution Law -- 9.4.5 Partition Function -- 9.4.6 Thermodynamic Properties -- 9.5 Statistical and Macroscopic Thermodynamics -- Summary -- Exercises -- Review Problems -- Problems for Practice -- Appendix One: Tables -- Appendix Two: Additional Problems -- Appendix Three: List of Formulae -- Appendix Four: Answers to Multiple-choice Questions -- Bibliography -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books